Strategi Kampanye Program Gerakan Masyarakat Hidup Sehat (GERMAS) Dinas Kesehatan Kota Bandung - Mochammad Rafy Raihan; Dadan Mulyana (UNISBA Press, 2022)
Abstract. In every government, including related agencies, including the Bandung City Health Office, of course there are programs that must be implemented that must be directly felt and reach the community and realize these programs effectively and efficiently. community problems and the thing that is very important so that the information or knowledge received must be received properly and intact is Vaccination. There is a lot of confusing information about vaccinations, including for parents. In this study taken from key informants and supporting informants. The Bandung City Health Office program is packaged in the